Understanding the capabilities for digital innovations from a digital technology perspective - Florian Wiesböck; Thomas Hess (Ludwig-Maximilians-Universität München, Institut für Wirtschaftsinformatik und Neue Medien (WIM), 2018)
With this study, we want to take a first step in this direction and try to develop a basic understanding of the capabilities for digital innovations (henceforth: digital innovation capabilities (DIC)) from a digital technology perspective. Such a perspective argues that digital innovations are based on digitalization and digital transformation capabilities (Wiesböck 2018). Hence, the aim of this paper is to develop a digital technology-centered theoretical conceptualization of an organization's DIC. This way, we want to answer the following research question: How do an organization's digitalization capabilities and digital transformation capabilities define an organization's digital innovation capabilities?
Keywords: 650